PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMA NEGERI 4 MAKASSAR - Arifin, Rahmi Nurul; Bunyamin, Andi; Mustamin; Syahid, Akhmad; Nengsih, Ratika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the extent of the influence of the Project-Based Learning model on student learning outcomes in Islamic Religious Education and Character Building at SMA Negeri 4 Makassar. The main focus of this study is driven by the importance of innovation in the learning process, which emphasizes not only the cognitive domain but also student engagement through project completion. The research method employed is quantitative, utilizing a positivism approach to measure the influence between two or more variables. The population for this study comprises all 432 twelfth-grade students, with a sample size determined at 82 students selected through the cluster sampling technique. Data collection was carried out using a Likert-scale questionnaire and documentary study. The data analysis techniques applied include classical assumption tests, multiple linear regression analysis, and hypothesis testing via t-test and F-test. The results of the data analysis indicate that partially, the three indicators of the independent variable namely project planning (X1), project execution (X2), and project presentation (X3) have a significant influence on student learning outcomes (Y). Simultaneously, the implementation of the Project-Based Learning model exerts a significant impact on learning outcomes, with a coefficient of determination (R2) of 0.534. This indicates that the model's contribution to explaining the variance in learning outcomes is 53.4%, while the remaining 46.6% is determined by other factors outside this research model. Based on the effective contribution values, the project planning indicator (X1) provides the most dominant contribution at 22.24%, followed by project execution (X2) at 16.82%, and project presentation (X3) at 14.34%. Therefore, it can be concluded that the project-based learning model has an influence on student learning outcomes in the subjects of Islamic Religious Education and Character Education at SMA Negeri 4 Makassar.